THE ROLE AND SIGNIFICANCE OF THE REGIONAL INVESTMENT ENVIRONMENT IN ATTRACTING FOREIGN INVESTMENTS TO THE ECONOMY (Conferencea, 2023)
Investment environment (or investment environment) is a concept used in a very broad sense, which includes all the problems and issues that are taken into account by the investor. The investor evaluates the favorable and unfavorable aspects of investing in a certain country, as well as the ideology, politics, economy and culture of the country in which he wants to invest his capital [1].